The market resources method for solving dynamic optimization problems - Ayşe Kabukçuoğlu; Enrique Martínez-García (Koç University-TÜSİAD Economic Research Forum (ERF), 2016)
We introduce the market resources method (MRM) for solving dynamic optimization problems. MRM extends Carroll's (2006) endogenous grid point method (EGM) for problems with more than one control variable using policy function iteration. The MRM algorithm is simple to implement and provides advantages in terms of speed and accuracy over Howard's policy improvement algorithm. Codes are available.
Keywords: C6; C61; C63; C68; 330; DSGE models; Computational methods; Policy function iteration; Endogenous grid